Safety of antiepileptic drugs in children and young people: A prospective cohort study. (March 2018) - Egunsola, Oluwaseun; Choonara, Imti; Sammons, Helen M.; Whitehouse, William P.
Highlights: Levetiracetam was the most common antiepileptic drug in this study. Levetiracetam and carbamazepine were better tolerated than sodium valproate. Monotherapy was the most common treatment regimen. Abstract: Purpose: This study aims to describe the incidence of adverse drug reactions (ADRs) in children receiving antiepileptic drugs (AEDs) and compare ADRs to the individual drugs when given as monotherapy. Method: Paediatric patients (≤18 years old) were enrolled for this prospective observational study over a 6-month period, between September 2015 and March 2016. Adverse reactions to antiepileptic drugs (AEDs) were elicited at the time of enrolment and after 3 months using the Paediatric Epilepsy Side Effects Questionnaire. Results: A total of 1139 suspected ADRs were reported in 124 participants. Eighteen different AEDs were prescribed. Sixty-six children (53%) were receiving AED monotherapy at the time of recruitment; 34/66 (52%) of whom received new generation AEDs. Levetiracetam was the most frequently prescribed AED (62/124, 50%). When only children receiving AED monotherapy were considered, fatigue, drowsiness, weight gain, dizziness were less likely with levetiracetam (p < .01). Slow thinking and decreased concentration were less likely with levetiracetam or carbamazepine than valproic acid (p < .05). Five patients (four on polytherapy) discontinued AED treatment due to ADRs and 2 had a dose reduction. Conclusions: Levetiracetam and carbamazepine were better tolerated than sodium valproate.